Piezoacoustics for precision control of electrons floating on helium - H. Byeon (Nature Portfolio, 2021)
Hybrid devices based on electrons on helium may find application in quantum devices. Here the authors demonstrate surface acoustic wave driven acoustoelectric transport of electrons on superfluid helium.